2007
DOI: 10.1203/pdr.0b013e318045be6d
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Infection of Human Syncytiotrophoblast Cells Strongly Interferes with Expression of Genes Involved in Placental Differentiation and Tissue Integrity

Abstract: ABSTRACT:The principle route of acquisition of cytomegalovirus (CMV) for the fetus is believed to be via the placenta. We subjected purified cytotrophoblast cells obtained from full-term placentas to CMV infection and examined placental gene expression using microarray analyses. Cytotrophoblast cells purified from term placentas differentiated in vitro into a multinucleated syncytium that could be productively infected with CMV, with peak virus titers of approximately 10 4 plaque-forming units (PFU)/mL identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…Indeed, HCMV DNA and gene expression has been found in clinical samples taken from placentas early and late in gestation (45,50,54,68). Accumulating experimental and clinical evidence indicates that, in addition to serving in viral transmission, the placenta may be actively injured by HCMV, conceivably contributing to the observed IUGR and fetal disease (1,50,59,60). The placenta is a chimeric organ, containing both maternal and fetal structures (43) (Fig.…”
mentioning
confidence: 99%
“…Indeed, HCMV DNA and gene expression has been found in clinical samples taken from placentas early and late in gestation (45,50,54,68). Accumulating experimental and clinical evidence indicates that, in addition to serving in viral transmission, the placenta may be actively injured by HCMV, conceivably contributing to the observed IUGR and fetal disease (1,50,59,60). The placenta is a chimeric organ, containing both maternal and fetal structures (43) (Fig.…”
mentioning
confidence: 99%
“…Schleiss et al (2007) found repression of MMP-3 in syncitiotrophoblasts and suggested that HCMV down-regulated genes associated with extracellular matrix formation and stabilization. Yamamoto-Tabata et al (2004) has also found a down-regulation of MMP-2 in HUVECS, uterine microvascular endothelial cells, fibroblasts and cytotrophoblasts and of MMP-9 in cytotrophoblasts and HUVEC upon infection with HCMV.…”
Section: Discussionmentioning
confidence: 95%
“…HCMV infection has been reported to hinder placental differentiation, to affect tissue integrity and to elicit a proinflammatory response (Benard et al, 2014;Chou et al, 2006;Schleiss et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations